The influence of complex fermentation broth on denitrification of saline sewage in constructed wetlands by heterotrophic nitrifying/aerobic denitrifying bacterial communities. (February 2018) - Fu, Guiping; Yu, Tianyu; Huangshen, Linkun; Han, Jingyi
Highlights: Higher denitrification rate of saline sewage is achieved in constructed wetlands. Complex fermentation broth is from waste clogging deposits and withered plants. Heterotrophic nitrifying–aerobic denitrifying bacteria dominate middle/upper layers. Obligate halophilic denitrifiers ( Zobellella sp.) are enriched and acclimatized. Limiting factors (salinity/insufficient organic C) of denitrification are overcome. Abstract: An experimental vertical-flow constructed wetland (CW) was tested to treat salt-containing sewage. CW clogging deposits and withered Pontederia cordata L. were collected into a complex fermentation broth to serve as the carbon source and its effects on the denitrification capacity and microbial composition of the CW were examined. Addition of the complex fermentation broth into the CW influent (1.8% salinity) led to high removal efficiencies of NH4 + -N > 99.82 ± 0.00% and TN > 90.39 ± 0.05%. Heterotrophic nitrifiers and aerobic denitrifiers were entirely dominant in the middle and upper layers of the CW, where obligate halophilic, aerobic denitrifiers Zobellella occurred. The CW successfully cultivated and enriched heterotrophic nitrifying–aerobic denitrifying bacteria, overcoming the effects of salinity and insufficient organic carbon sources on the denitrification capacity of CW. This type of complex carbon sources can also facilitate the utilization of waste resources, such as CW clogging deposits and withered wetland plants.